2009
DOI: 10.1089/aid.2008.0236
|View full text |Cite
|
Sign up to set email alerts
|

Analysis ofpolIntegrase Sequences in Diverse HIV Type 1 Strains Using a Prototype Genotyping Assay

Abstract: A prototype assay was used to genotype integrase (IN) from 120 HIV-1-infected IN inhibitor-naive adults from Argentina, Brazil, Cameroon, South Africa, Thailand, and Uganda. Subtype designations based on analysis of pol

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
15
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 5 publications
3
15
0
Order By: Relevance
“…Previous genotypic studies on HIV-1 integrase revealed that several secondary mutations associated with resistance to integrase inhibitors, including V72I, L74I, E92Q, T97A, V151I, M154I/L, E157Q, V165I, V201I, I203M, T206S, and S230N, were frequently detected in many subtypes and CRFs of HIV-1 derived from drug-naive patients in many countries, including Thailand, Cambodia, Vietnam, and the United States. [9][10][11][12][13] In these reports, drug resistance-associated mutations appeared due to natural polymorphisms at amino acid positions 72, 74,97,112,119,125,128,138,151,153,154,155,156,157,163,165,201,203,206, and 230 of HIV-1 integrase, coinciding with our results. [9][10][11][12][13] In addition to these secondary mutations, 40% (16/40) of the CRF01_AE in this study possessed an unusual tetrapeptide insertion (QNME/A) in the C-terminus of the integrase.…”
supporting
confidence: 92%
“…Previous genotypic studies on HIV-1 integrase revealed that several secondary mutations associated with resistance to integrase inhibitors, including V72I, L74I, E92Q, T97A, V151I, M154I/L, E157Q, V165I, V201I, I203M, T206S, and S230N, were frequently detected in many subtypes and CRFs of HIV-1 derived from drug-naive patients in many countries, including Thailand, Cambodia, Vietnam, and the United States. [9][10][11][12][13] In these reports, drug resistance-associated mutations appeared due to natural polymorphisms at amino acid positions 72, 74,97,112,119,125,128,138,151,153,154,155,156,157,163,165,201,203,206, and 230 of HIV-1 integrase, coinciding with our results. [9][10][11][12][13] In addition to these secondary mutations, 40% (16/40) of the CRF01_AE in this study possessed an unusual tetrapeptide insertion (QNME/A) in the C-terminus of the integrase.…”
supporting
confidence: 92%
“…For this analysis, we included data from several recently published studies with large numbers of IN sequences from INI-naïve patients. [11][12][13][14][15] We combined the IN sequences of the 150 patients we describe here with sequences from 4170 previously reported INInaïve patients published in GenBank as of April 15, 2010 to calculate the frequency with which each mutation has been reported at each IN position. Figure 1 shows the proportions of all mutation present in 0.5% of the 4470 INI-naïve patients.…”
Section: Updated Analysis Of Hiv-1 In Polymorphism In Ini-naïve Patientsmentioning
confidence: 99%
“…[11][12][13][14] In addition, such integrase mutations were detected in many subtypes and CRFs of HIV-1 including CRF01_AE viruses. 4,[13][14][15] In these reports, drug resistance-associated mutations were suggested to have appeared due to natural polymorphisms at amino acid positions 72, 74,97,112,119,125,128,138,151,153,154,155,156,157,163,165,201,203,206, and 230 of HIV-1 integrase. 4,[11][12][13][14] According to this information, all secondary mutations detected in this study might be due to natural polymorphism.…”
mentioning
confidence: 99%
“…4,[13][14][15] In these reports, drug resistance-associated mutations were suggested to have appeared due to natural polymorphisms at amino acid positions 72, 74,97,112,119,125,128,138,151,153,154,155,156,157,163,165,201,203,206, and 230 of HIV-1 integrase. 4,[11][12][13][14] According to this information, all secondary mutations detected in this study might be due to natural polymorphism. Nevertheless, we consider that further surveillance studies are necessary to identify drug resistance-associated integrase mutations in HIV-1-infected, drug-naive Thai patients.…”
mentioning
confidence: 99%